PREFERENSI KONSUMEN OLAHAN TRADISIONAL KOPI ROBUSTA WILAYAH GRESIK - Hary Sastrya Wanto; Koesriwulandari Koesriwulandari; Miftakhul Hidayat (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabay, 2023)
ABSTRACTCoffee is one of the plantation commodities that will have relatively high economic value among other plantation plants and play an important role as a source of foreign exchange for the country. Coffee not only plays an important role as a source of foreign exchange but also a source of income for no less than one and a half million coffee farmers in Indonesia. What coffee attributes have a relationship with consumers in Mbah Bedo warkop Analyze the effect of quality attributes on product preference on buyer decisions at Mbah Bedo warkop. The results of this study can provide an overview of the impact of product quality, service quality, and price on purchasing decisions at Mbah Bedo as a result can be used as an assessment on managing products, services, and prices for the better in the future. Chi Square, which uses the integrity match method to test critical contrast between a large number of objects (noticed) or (expected) with respect to invalid speculation, which is perhaps one of the most prominent models for deciding attitudes on objects. Coffee taste attributes are robusta coffee attributes that consumers believe are the most enjoyed, according to the results of primary data analysis. Consumers believe that the taste of coffee is the most important factor, influencing their decision to consume robusta coffee in the region. Because taste is the most important thing that you want to enjoy and consume when consumers will buy robusta coffee.Keywords : Taste Satisfaction, Texture, PackagingABSTRAKKopi merupakan salah satu komoditas perkebunan yang memiliki nilai ekonomi relatif tinggi diantara tanaman perkebunan lainnya dan berperan penting sebagai sumber devisa negara. Kopi tidak hanya berperan penting sebagai sumber devisa negara tetapi juga menjadi sumber pendapatan bagi tidak kurang dari satu setengah juta petani kopi di Indonesia. Apa hubungan atribut kopi dengan konsumen pada warkop Mbah Bedo? Menganalisis pengaruh atribut kualitas terhadap preferensi produk terhadap keputusan pembeli pada warkop Mbah Bedo. Hasil penelitian ini dapat memberikan gambaran mengenai pengaruh kualitas produk, kualitas pelayanan, dan harga terhadap keputusan pembelian pada Mbah Bedo sehingga hasilnya dapat dijadikan sebagai penilaian dalam pengelolaan produk, pelayanan, dan harga menjadi lebih baik kedepannya. . Chi Square, yang menggunakan metode kecocokan integritas untuk menguji kontras kritis antara sejumlah besar objek (yang diperhatikan) atau (yang diharapkan) sehubungan dengan spekulasi yang tidak valid, yang mungkin merupakan salah satu model paling menonjol untuk menentukan sikap terhadap objek. Atribut rasa kopi merupakan atribut kopi Robusta yang diyakini paling disukai konsumen berdasarkan hasil analisis data primer. Konsumen meyakini bahwa cita rasa kopi merupakan faktor terpenting yang mempengaruhi keputusan mereka mengonsumsi kopi Robusta di suatu daerah. Karena rasa merupakan hal terpenting yang ingin dinikmati dan dikonsumsi ketika konsumen akan membeli kopi Robusta.Kata Kunci: Kepuasan Rasa, Tekstur, Kemasan